Multi-Target Screening and Experimental Validation of Natural Products from Selaginella Plants against Alzheimer's Disease - Deng, Yin-Hua; Wang, Ning-Ning; Zou, Zhen-Xing; Zhang, Lin; Xu, Kang-Ping; Chen, Alex F.; Cao, Dong-Sheng; Tan, Gui-Shan (Frontiers in Pharmacology, 2017)
Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative disorder which is considered to be the most common cause of dementia. It has a greater impact not only on the learning and memory disturbances but also on social and economy. Currently, there are mainly single-target drugs for AD treatment but the complexity and multiple etiologies of AD make them difficult to obtain desirable therapeutic effects. Therefore, the choice of multi-target drugs will be a potential effective strategy in AD treatment. To find multi-target active ingredients for AD treatment from Selaginella plants, we firstly explored the behaviors effects on AD mice of total extracts (TE) from Selaginella doederleiniion by Morris water maze test and found that TE has a remarkable improvement on learning and memory function for AD mice. And then, multi-target SAR models associated with AD-related proteins were built based on Random Forest (RF) and different descriptors to preliminarily screen potential active ingredients from Selaginella. Considering the prediction outputs and the quantity of existing compounds in our laboratory, 13 compounds were chosen to carry out the in vitro enzyme inhibitory experiments and 4 compounds with BACE1/MAO-B dual inhibitory activity were determined. Finally, the molecular docking was applied to verify the prediction results and enzyme inhibitory experiments. Based on these study and validation processes, we explored a new strategy to improve the efficiency of active ingredients screening based on trace amount of natural product and numbers of targets and found some multi-target compounds with biological activity for the development of novel drugs for AD treatment.